Treatment Decision-Making Capacity in Forensic vs Non-forensic Psychiatric Patients: A European Comparison. Issue 1 (16th June 2022) - Marazia, Chantal; Rucci, Paola; Fangerau, Heiner; Voßberg, Dilara; Rolfes, Vasilija; Iozzino, Laura; Iommi, Marica; Gosek, Pawel; Heitzman, Janusz; Ferrari, Clarissa; Macis, Ambra; Markiewicz, Inga; et al.
Abstract: Background: Consent to treatment is a cornerstone of medical ethics and law. Nevertheless, very little empirical evidence is available to inform clinicians and policymakers regarding the capacities of forensic patients with schizophrenia spectrum disorders (SSDs) to make decisions about their treatment, with the risk of clinical and legal inertia, silent coercion, stigmatization, or ill-conceived reforms. Study Design: In this multinational study, we assessed and compared with treatment-related decisional capacities in forensic and non-forensic patients with SSD. 160 forensic and 139 non-forensic patients were used in Austria, Germany, Italy, Poland, and England. Their capacity to consent to treatment was assessed by means of the MacArthur Competence Assessment Tool for Treatment (MacCAT-T). Multiple generalized linear regression models were used to identify the socio-demographic and clinical variables associated with MacCAT-T scores. Study Results: In total, 55 forensic (34.4%) and 58 non-forensic patients (41.7%) showed high treatment-related decisional capacity, defined as scoring ≥75% of the maximum scores for the understanding, appreciation and reasoning, and 2 for expressing a choice. Forensic patients showed differences in their capacity to consent to treatment across countries. Of all socio-demographic and clinical variables, only "social support" was directly relevant to policy. Conclusions: Forensic patients have treatment-related decisional capacities comparable with their non-forensic counterparts. Social contacts might provide a substantial contribution towards enhancing the decisional autonomy of both forensic and non-forensic patients, hence improving the overall quality and legitimacy of mental health care.